The Conceptualization of a Crime Event as a Process to Analyze Crime Commission and Behavioral Consistency in Serial Sexual Assaults - Schanz, Kimberley R (2017)
This project examined the two main questions of why and when behaviors change. In the course of five studies, four aims were addressed. The first aim examined why behaviors change by examining whether the behavioral subtypes of control, sex, and violence could differentiate offenses within the elements of a crime (e.g. the offender, victim, and situation. The second aim addressed when behaviors change by examining whether the behavioral subtypes of control, sex, and violence could differentiate offenses within the temporal phases of a crime (e.g. before, during, and after the crime). The third aim examined which behaviors to use as the basis of the proposed three ways to examine behavioral consistency. Finally, the fourth and last aim was to use behavioral trajectories to explore patterns of (e.g. when) and possible explanations for (e.g. why) behavioral change. Multiple techniques of multidimensional scaling as well as behavioral trajectories were used. Results show that while the behavioral subtypes of control, sex, and violence were unable to differentiate between offenses as hypothesized, there were other thematic structures that were shown to do so. Patterns of both behavioral consistency and predictable change were found using behavioral trajectories, and potential behavioral co-occurrences to explain those changes were also determined